A Novel to Method to Measure Food Waste: The Mobile Food Record - Kaitlin Danible; Chloe Panizza; Carol Boushey; Deborah Kerr; Fengqing Zhu; Jinan C. Banna ([TEST] Journal of Extension, 2021)
The mobile food record (mFR) is a novel app that allows for the tracking of individual food waste and addresses the limitations of current methods to accurately quantify food waste. Extension educators may use data from the mFR to create educational initiatives for food waste prevention and education that may be implemented in settings such as schools and universities. The mFR is an innovative application that simplifies the process of collecting food-based data and accurately quantifying food waste for use in Extension.
Keywords: food waste; food record